2021
DOI: 10.1007/s00281-021-00871-y
|View full text |Cite
|
Sign up to set email alerts
|

The mucosal immune system and IgA nephropathy

Abstract: The precise pathogenesis of immunoglobulin A nephropathy (IgAN) is still not clearly established but emerging evidence confirms a pivotal role for mucosal immunity. This review focuses on the key role of mucosa-associated lymphoid tissue (MALT) in promoting the onset of the disease, underlying the relationship among microbiota, genetic factors, food antigen, infections, and mucosal immune response. Finally, we evaluate potential therapies targeting microbes and mucosa hyperresponsiveness in IgAN patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 100 publications
0
38
0
Order By: Relevance
“…Yuan et alfound that the gene of CXCL2 was crucially associated with the immune infiltration between CD and IgA nephropathy [ 29 ]. Alteration of the microbiota could lead to ecological dysregulation, which regulated immune-mediated IBD and IgA nephropathy [ 30 , 31 ]. In a study, a reduction in circulating IgA complexes and proteinuria was observed in patients with IgA nephropathy on a gluten-free diet for 6 months to 4 years [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et alfound that the gene of CXCL2 was crucially associated with the immune infiltration between CD and IgA nephropathy [ 29 ]. Alteration of the microbiota could lead to ecological dysregulation, which regulated immune-mediated IBD and IgA nephropathy [ 30 , 31 ]. In a study, a reduction in circulating IgA complexes and proteinuria was observed in patients with IgA nephropathy on a gluten-free diet for 6 months to 4 years [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“… 50 Therefore, aberrant mucosal immune response is considered to be involved in the pathogenesis of IgAN. 51 …”
Section: Discussionmentioning
confidence: 99%
“…Some of these cytokines can then cause podocyte injury and induce proteinuria. The figure refers to the pathogenesis of IgAN by Gesualdo et al 51 …”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the “first hit” is that individuals with a genetic susceptibility develop abnormal immune responses to common and environmental antigens, which leads to an increase of galactose-deficient IgA1 in circulation. A growing body of evidence suggests that abnormality of intestinal mucosal immunity plays an important role in IgAN [ 25 ]. Integrin alpha M (ITGAM) encodes the integrin alpha M chain (CD11b) and belongs to the integrin family.…”
Section: Discussionmentioning
confidence: 99%